2011
DOI: 10.1007/s11207-011-9781-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Shock Waves, EUV Waves, and Their Relation to CMEs. III. Shock-Associated CME/EUV Wave in an Event with a Two-Component EUV Transient

Abstract: On 17 January 2010, STEREO-B observed in extreme ultraviolet (EUV) and white light a large-scale dome-shaped expanding coronal transient with perfectly connected off-limb and on-disk signatures. Veronig et al. (2010, ApJL 716, 57) concluded that the dome was formed by a weak shock wave. We have revealed two EUV components, one of which corresponded to this transient. All of its properties found from EUV, white light, and a metric type II burst match expectations for a freely expanding coronal shock wave incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…However, the difference in the observed radial and lateral speeds could in principle result from different fast-mode speed profiles in the corresponding directions. Finally, Grechnev et al (2011) reached essentially the same conclusion using a 3D blast wave model which was in a very good agreement with the ground tracks of the wave dome both on-disk and off-limb. Other examples of wave domes can be seen in the events of 13 June 2010, 7 June 2011 and 4 August 2011.…”
Section: D Structure and Relationship With Cmessupporting
confidence: 71%
See 1 more Smart Citation
“…However, the difference in the observed radial and lateral speeds could in principle result from different fast-mode speed profiles in the corresponding directions. Finally, Grechnev et al (2011) reached essentially the same conclusion using a 3D blast wave model which was in a very good agreement with the ground tracks of the wave dome both on-disk and off-limb. Other examples of wave domes can be seen in the events of 13 June 2010, 7 June 2011 and 4 August 2011.…”
Section: D Structure and Relationship With Cmessupporting
confidence: 71%
“…The pulse broadening points also to a freely-propagating wave. Indeed, Grechnev et al (2011) found that a 3D model of a blast wave propagating in a medium with density stratification was broadly consistent with the ground track of 17 January 2010 (see also Veronig et al (2010)). Finally, MHD modeling of rotating sunspots by Selwa, Poedts, and DeVore (2012) showed that dome-like structures, similar to what is observed, could be generated.…”
Section: Kinematics Amplitudes and Dispersionmentioning
confidence: 66%
“…The piston could thus be attributed to the front of the CME itself, or the full CME bubble or loops, as has been reported by several observational studies (Patsourakos and Vourlidas, 2012). Some observational reports reinforce this picture (Kienreich, Temmer, and Veronig, 2009;Patsourakos and Vourlidas, 2009;Veronig et al, 2010;Grechnev et al, 2011b). If this is the case, the faster lobe of sectors 29 -34 could be related with a piston provided by a CME structure, probably stretched, non-radially rising, i.e.…”
Section: About the Origin Of The Shocksmentioning
confidence: 57%
“…The enhanced pressure behind the wavefront compresses the chromospheric plasma, which is observed as the down-up swing in Hα filtergrams, and recently detected as EUV redshifts (Harra et al 2011;Veronig et al 2011) or seen in EUV images (Liu et al 2012b). As the Alfvén speed increases with height in the low corona, it is expected that the wavefront of a coronal fastmode MHD wave is forwardly inclined toward the solar surface, which is observed in some limb events (e.g., Hudson et al 2003;Liu et al 2012b) and reproduced by numerical simulations (e.g., Wu et al 2001;Grechnev et al 2011). In a recent observation, an Hα Moreton wavefront is observed to be the ground track of a dome-shaped coronal shock front (Asai et al 2012;Shen & Liu 2012).…”
Section: Introductionmentioning
confidence: 71%